2021
DOI: 10.12968/jowc.2021.30.sup7.s28
|View full text |Cite
|
Sign up to set email alerts
|

Surgical reconstruction of pilonidal sinus disease with concomitant extracellular matrix graft placement: a case series

Abstract: Background: Pilonidal sinus disease (PSD) is a chronic inflammatory disease affecting the soft tissue of the sacrococcygeal region and remains a challenging disease for clinicians to treat. The optimal treatment for PSD remains controversial and recent reports describe several different surgical approaches offering different benefits. Approximately 40% of initial incision and drainage cases require subsequent surgery. Due to high recurrence rates and postoperative complications, a more complex revision surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Pilonidal sinus disease (PSD) commonly occurs in the sacrococcygeal area. It is regarded as a distressing disease and a challenge to clinicians owing to; the high morbidity of management methods, high recurrence rates, and several other complications 8,12 . This disease is multifactorial, and an abundant number of risk factors have been reported to be associated with its occurrence 12,13 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Pilonidal sinus disease (PSD) commonly occurs in the sacrococcygeal area. It is regarded as a distressing disease and a challenge to clinicians owing to; the high morbidity of management methods, high recurrence rates, and several other complications 8,12 . This disease is multifactorial, and an abundant number of risk factors have been reported to be associated with its occurrence 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…It is regarded as a distressing disease and a challenge to clinicians owing to; the high morbidity of management methods, high recurrence rates, and several other complications 8,12 . This disease is multifactorial, and an abundant number of risk factors have been reported to be associated with its occurrence 12,13 . In a study by Cevik et al, it was revealed that most of the affected individuals had spent a minimum of 8 hours a day sitting studying 7 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations